1991
DOI: 10.1063/1.106213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carrier transport on high-speed quantum well lasers

Abstract: We present a model for the dynamic response of quantum well lasers which shows that the carrier transport across the separate confinement heterostructure region and the barriers can be critical in determining the modulation bandwidth. We also show that, depending on the particular quantum well laser structure, a large part of the experimentally measured reduction in modulation bandwidth is due to transport factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…For single-QW lasers, the factor can vary by two times between 200-350 K [4]. The temperature insensitivity of the factor implies that the differential gain and the nonlinear gain suppression coefficient have a similar temperature dependence and cancel each other to maintain a temperature-insensitive ratio in InGaAsP-InP QW materials.…”
Section: Temperature Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…For single-QW lasers, the factor can vary by two times between 200-350 K [4]. The temperature insensitivity of the factor implies that the differential gain and the nonlinear gain suppression coefficient have a similar temperature dependence and cancel each other to maintain a temperature-insensitive ratio in InGaAsP-InP QW materials.…”
Section: Temperature Dependencementioning
confidence: 99%
“…Assuming a small-signal optical injection due to the external pump laser (4) where the test laser is biased at a dc current above threshold. The responses can be solved by assuming (5) (6) (7) and (8) where is the differential gain of the test laser, and is steady-state carrier density in the QW.…”
Section: Rate Equations For Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…In SQW's, Auger recombination losses can be significant [31]. Previously, in our work on the MLME model [16]- [17], Auger recombination was not included.…”
Section: Including Auger Recombinationmentioning
confidence: 99%
“…While the carrier capture and escape time constants used in the original "reservoir" model was described only phenomenologically, Nagarajan et al [Nagarajan 1991] attributed carrier diffusion across the SCH region as being a major contributor to the capture time, and classical thermionic emission as the major physical mechanism for carrier escape from the quantum well, as supported by experimental results from quantum well lasers with various SCH widths [Nagarajan 1991]. Futhermore, when one considers the rate equations involved in the transport in more detail, it was found that the effect of transport is more than just an increase gain compression -it has other consequences in terms of modifying the relaxation oscillation frequency and the shape of the response function [Nagarajan 1991] [Wu 1992].…”
Section: Introductionmentioning
confidence: 99%